AN ECONOMIC STUDY ON CHALLENGES AND OPPORTUNITIES IN IMPROVING THE INDIAN ECONOMY - SUNDARAM, K. MEENAKSHI (International Journal of Psychosocial Rehabilitation, 2020)
This paper reveals an economic study on challenges and opportunities in improving the Indian economy. India is the second country with largest population after China. India is a stable democracy. Its people are 80 percent Hindu, but it is also home to one of the world’s largest Muslim populations and other religions too. This is why, India is also called a secular country. India’s economic freedom score is 56.5, making its economy the 120th freest in the 2020 Index. Its overall score has increased by 1.3 points, led by an increase in the business freedom score. India is ranked 28th among 42 countries in the Asia–Pacific region, and its overall score is well below the regional and world averages. India’s diverse economy encompasses traditional village farming, modern agriculture, handicrafts, and a wide range of modern industries. Capitalizing on its large educated, English-speaking population, India has become a major exporter of information technology services, business outsourcing services, and software workers. The Indian economy has languished in the mid-range of the mostly unfree category for nearly two decades. GDP growth over the past five years, however, has been robust. As the country continues to benefit from the effects of economic liberalization, economic growth has been driven by higher private domestic consumption. This paper is alsoanalysing and discusses about the growth in the value of GDP which helps the raise of Indian economy and also considering the policies by the Indian government which made an impact on Indian economy. Also discusses about the effects of Indian economy by the financial wireless transfers from our country to the other countries.